Discovery of Secondary Metabolites from the Sponge-Derived Fungus Aspergillus templicola - Kai Li; Yue Zhang; Lei Li; Sen Wang; Cili Wang; Pinglin Li (Marine Drugs, 2025)
Combining biosynthetic gene cluster analysis with the OSMAC strategy, fractionation of the fermentation extract of Aspergillus templicola from the sponge Agelas sp. led to the isolation of four novel cytochalasins, colachalasins J–M (1–4), a novel cyclic pentapeptide, avellanin P (5), together with five known compounds (6–10). The structures of 1–9 were elucidated using spectroscopic data, single crystal X-ray diffraction, and Marfey’s analysis. Compound 2 exhibited potent anti-inflammatory activity in zebrafish assays. Additionally, Compounds 4 and 6 showed modest cytotoxicity against several human cancer cell lines with IC50 values ranging from 2.6 to 11.2 μm.